The use of plant (Citrullus colocynthis) in alternative medicine: (Historical facts - Geographical view) - Abood, Abdallah Sabaar; Waheed, Hussam Kanaan (Al-Adab Journal, 2022)
Alternative medicine is one of the most important choices for humans, as many people are going to live closer to nature, because they have seen good results for most herbs that replace the chemical drugs that have greatly affected the human body. The research investigates the historical facts of alternative medicine, the use of Citrullus colocynthis, the treatment of many diseases, the geographical distribution of plants in Iraq, and the proposal to invest in plants in Iraq.